Iron overload impact on peripheral blood cells, lymphocytes and karyotypes in newly diagnosed myelodysplastic syndromes (MDS) patients: a single-center retrospective analysis - Lixiang Duan; Wenjun Yu; Xiaolin Jiao; Ying Sun; Yao Fang Ma; Le Li; Zeqiang Nie; Dan Zhao (All Life)
We conducted a retrospective analysis of 68 newly diagnosed myelodysplastic syndrome (MDS) patients who were treated in the Department of Hematology at Yuncheng Central Hospital affiliated to Shanxi Medical University from October 2017 to March 2022. Based on the serum ferritin (SF) level, the newly diagnosed MDS patients were divided into two groups: iron overload (IOL) group (SF > 1000 ng/mL) and non-iron overload (NIOL) group(SF ≤ 1000 ng/mL). General clinical data, peripheral blood cells, lymphocyte subsets and marrow karyotypes were compared. We found that MDS patients with IOL had lower hemoglobin (Hb), lower reticulocyte (RET) counts, and lower absolute natural killer (NK) cell counts compared with NIOL group (p < 0.05). The correlation analysis also showed a negative correlation between the NK cell counts and SF level (r = −0.270, P = 0.026). Furthermore, we found IOL group had higher incidence of complex and poor karyotypes. In conclusion, we found that IOL is correlated with anemia in MDS patients, which may lead to a decrease in T lymphocyte cells, especially in NK cells, that play a role in the immune pathogenesis of MDS, thereby suppressing immune surveillance function. Additionally, IOL may contribute to the pathogenesis of MDS by affecting karyotypes.